A Comparative Analysis of Transitivity System in Model and Student Descriptive Texts - Wibowo, Enggar Pangesti; Lestari, Ayu; Adrian, Merry (JURNAL Al-AZHAR INDONESIA SERI HUMANIORA, 2024)
Researches on ideational meaning have been widely reported, but rarely do they compare transitivity analysis systems on two similar texts. The aim of the study deals with the transitivity system of the descriptive texts of the model text taken from a TOEFL exercises book and the student’s text written by a tenth grade student of SMA Islam Al Azhar 15 Semarang. It also explores how the understanding of experiential grammar informs pedagogical practices. The research approach of the study was descriptive qualitative completed by textual analysis using Halliday’s SFL theory. The result of the transitivity system shows that the model text and the student’s text employed different types of processes. However, both texts present a similar transitivity pattern in the dominance of material processes and circumstances of location. One incomplete clause in the student’s text caused the attributive process not to appear. All in all, the main linguistic features of descriptive text, relational processes, are not accurately employed in the texts. Knowledge of experiential grammar brings potential benefits for both learning and teaching. It enhances student learning by providing an understanding of authorial intent and grammatical structure, and empowers educators to create useful instructional approaches to improve students' writing and critical thinking skills.Keywords - Descriptive Text, Ideational Meaning, SFL, Transitivity System.